The Mas20p and Mas70p subunits of the protein import receptor of yeast mitochondria interact via the tetratricopeptide repeat motif in Mas20p: evidence for a single hetero-oligomeric receptor. - Haucke, V (1996)
Protein import into yeast mitochondria is mediated by four integral outer membrane proteins which function as import receptors. These proteins (termed Mas20p, Mas22p, Mas37p and Mas70p) appear to exist as two subcomplexes: a Mas37p-Mas70p heterodimer and a less well characterized Mas20p-Mas22p complex. The subcomplexes interact functionally during protein import, but it has remained uncertain whether they are in direct contact with each other in vivo. Here we show that Mas20p and Mas70p can be cross-linked in intact mitochondria, or co-immunoprecipitated from digitonin-solubilized mitochondria. Furthermore, the cytosolic domains of these two proteins interact in the 'two-hybrid' system. Association of Mas20p and Mas70p is virtually abolished by a mutation in the single tetratricopeptide motif in Mas20p. This mutation specifically inhibits import of precursors that are first recognized by Mas37p-Mas70p and only then transferred to Mas20p-Mas22p. We conclude that the two receptor subcomplexes of the mitochondrial protein import receptor interact in vivo via their Mas20p and Mas70p subunits and that this interaction is functionally important.